Penggunaan Uselearn Sebagai Metode Evaluasi Usability untuk E-Learning - Dian Palupi Restuputri; Wahyu Fitrianda Mufti (Jurnal Teknik Industri, 2014)
This study aimed to evaluate E-learning using uselearn method. Uselearn is usability assessment method to assess E-learning from variable quality and usability. The questionnaire was given to 101 participants. The participants were given a questionnaire according with 12 dimensions of uselearn. Structural Equation Modelling (SEM) was used to validate the result of quantitative statistic. The results obtained after processing the data using SEM formed 10 new usability dimensions namely Consistency and Functionality (CF), Error Prevention (EP), Visibility (VIS), Flexibility (FLEX), Accessibility (AC), Memorability (MEMO), Completeness (COM ), Reducing redundancy (RR), Interactivity, Feedback and Help (IFH), and Assessment Strategy (AS). From the analysis obtained the lowest usability index values for the dimensions of Interactivity Feedback and Help (IFH), Reducing redundancy (RR), Completeness (COM) and Error Prevention (EP). Improvements that can be done is to improve the appearance of the icon and menu additions, as well as setting the E-learning website.